THE ROLE OF JOKES IN SHAPING SOCIAL AND CULTURAL INTERACTIONS (Modern education and development, 2024)
Jokes play a multifaceted role in human communication, acting as a tool for social bonding, cultural expression, and even conflict resolution. This article explores the pragmatics of jokes, examining their linguistic, sociocultural, and psychological dimensions. Through an interdisciplinary approach, it highlights how jokes contribute to shaping social norms, reinforcing group identity, and navigating power dynamics. By understanding the underlying mechanisms of humor, we gain insight into its profound influence on social and cultural interactions.